"Which pass is better?" Novel approaches to assess passing effectiveness in elite soccer - Rein, R.; Raabe, D.; Memmert, D. (Human Movement Science, 2017)
Passing behaviour is a key property of successful performance in team sports. Previous investigations however have mainly focused on notational measurements like total passing frequencies which provide little information about what actually constitutes successful passing behaviour. Consequently, this has hampered the transfer of research findings into applied settings. Here we present two novel approaches to assess passing effectiveness in elite soccer by evaluating their effects on majority situations and space control in front of the goal. Majority situations are assessed by calculating the number of defenders between the ball carrier and the goal. Control of space is estimated using Voronoi-diagrams based on the player`s positions on the pitch. Both methods were applied to position data from 103 German First division games from the 2011/2012, 2012/2013 and 2014/2015 seasons using a big data approach. The results show that both measures are significantly related to successful game play with respect to the number of goals scored and to the probability of winning a game. The results further show that on average passes from the mid-field into the attacking area are most effective. The presented passing efficiency measures thereby offer new opportunities for future applications in soccer and other sports disciplines whilst maintaining practical relevance with respect to tactical training regimes or game performances analysis. AUTORREFERAT